Singapore's regionalisation strategy : progress and prospects. - Siow, Wendy Yen Li. (2008)
This study examines the degree of regionalisation attained so far since 1993. An empirical research is performed which involves the background, rationale and assessment of the regionalisation progress. The study makes use of certain ratios to analyze world regions and eight individual countries.